2019
DOI: 10.1038/s41598-018-36888-x
|View full text |Cite
|
Sign up to set email alerts
|

SP1 and RARα regulate AGAP2 expression in cancer

Abstract: AGAP2 (Arf GAP with GTP-binding protein-like domain, Ankyrin repeat and PH domain 2) isoform 2 is considered a proto-oncogene, but not much is known about AGAP2 gene expression regulation. To get some insight into this process, AGAP2 proximal promoter was cloned and characterised using reporter assays. We have identified SP1 as a transcription factor bound to AGAP2 promoter and required for AGAP2 expression in two different types of cancer cells (KU812, a chronic myeloid leukaemia cell line; and DU145, a prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…Additionally, the promoter region of AGAP2 has also been found to be hypermethylated in GDM-born offspring [40], which is similar to our findings in RES male offspring [36]. Given the key role of HOX genes in cell differentiation, function, and cancer [41] as well as AGAP2 as a proto-oncogene [42], additional work needs to be conducted to determine if changes in the expression of these genes could alter the histology and function of the pancreas tissue.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, the promoter region of AGAP2 has also been found to be hypermethylated in GDM-born offspring [40], which is similar to our findings in RES male offspring [36]. Given the key role of HOX genes in cell differentiation, function, and cancer [41] as well as AGAP2 as a proto-oncogene [42], additional work needs to be conducted to determine if changes in the expression of these genes could alter the histology and function of the pancreas tissue.…”
Section: Discussionsupporting
confidence: 82%
“…The transcription factor Sp1 regulates the transcription of several genes 43 45 . Takagi et al ., used primary human keratinocytes to analyze the structure of the human ATP2A2 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Reporter assays have identified the nucleotides -246/+36 in AGAP2 DNA sequence containing the minimal AGAP2 promoter region involved in AGAP2 expression in both chronic myeloid leukemia and prostate cancer human cell lines. Specificity protein 1 (SP1) transcription factor has been found to be bound to this fragment and to be required for AGAP2 expression in these tumoral cell lines [25]. Furthermore, the AGAP2 promoter fragment -475/-246 contains a functional direct repeat of two motifs (G/AGTTCA) separated by 5 bp (DR5) binding site with a retinoic acid response element (RARE), which seems to be functional as the addition of all-trans retinoic acid (ATRA) induced AGAP2 promoter activity and increased AGAP2 expression.…”
Section: Regulation Of Agap2 Expression and Activitymentioning
confidence: 99%
“…Chromatin immunoprecipitation assays confirmed that the nuclear receptors RARα (retinoic acid receptor α) and RXRα (retinoid X receptor α) and the lysine acetyl transferase acetyl transferase P300/CBP-associated factor (PCAF) were present at the promoter under conditions of AGAP2 expression in prostate cancer cells. And it was proposed that ATRA might lead to the recruitment of PCAF and perhaps increased SP1 binding to AGAP2 promoter, thereby leading to increased AGAP2 levels in cancer cells [25].…”
Section: Regulation Of Agap2 Expression and Activitymentioning
confidence: 99%
See 1 more Smart Citation